Parry⁃Romberg syndrome: two cases report and literature review - SHA Yu⁃hui; MAO Chen⁃hui; LI Sheng⁃de; ZHOU Li⁃xin; NI Jun (Chinese Journal of Contemporary Neurology and Neurosurgery, 2023)
Objective Parry⁃Romberg syndrome is a rare disease characterized by unilateral facial progressive atrophy accompanied by ipsilateral intracranial lesions and/or cerebral atrophy, this article is aimed to analyze the clinical, radiological and pathological features of patients with Parry ⁃ Romberg syndrome and explore the microvascular mechanism in the pathogenesis of the disease, to provide reference for understanding the nature of disease. Methods and Results The age of onset was 27 and 17 years old of the 2 patients respectively. Case 1 initially presented with left⁃sided progressive hemifacial atrophy and developed paroxysmal pain, twitch and numbness on the left face. Case 2 presented with a band ⁃ like alopecia in the left fronto⁃parietal area with cutaneous atrophy, and sudden right limb mild hemiplegia. The MRI of Case 1 revealed a space⁃occupying lesion in the left frontal and insular lobes without enhancement. The MRI of Case 2 showed recent lacunar cerebral infarction in left posterior limb of internal capsule. The histopathological examination of Case 1 showed hemorrhage, microvascular thrombosis, fibrinoid necrosis of vascular walls and mild peri⁃microvascular chronic inflammatory cell infiltration, who was irresponsive to prednisone. Case 2 received aspirin and remained free from any cerebrovascular event at his one⁃year⁃ follow up. Conclusions The microvascular mechanism may be the pathogenesis of Parry ⁃ Romberg syndrome, and the antiplatelet therapy may be an optional schedule for stroke prevention and treatment in patients with Parry⁃Romberg syndrome.